2021
DOI: 10.1371/journal.pone.0260642
|View full text |Cite
|
Sign up to set email alerts
|

Do manual therapies have a specific autonomic effect? An overview of systematic reviews

Abstract: Background The impact of manual therapy interventions on the autonomic nervous system have been largely assessed, but with heterogeneous findings regarding the direction of these effects. We conducted an overview of systematic reviews to describe if there is a specific autonomic effect elicited by manual therapy interventions, its relation with the type of technique used and the body region where the intervention was applied. Methods We conducted an overview according to a publicly registered protocol. We se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 110 publications
(298 reference statements)
0
22
0
Order By: Relevance
“…In systematic review studies Roura et al ( 31 ) found that manual therapy may affect both the sympathetic and parasympathetic systems, but the results were inconsistent, the methodology was heterogeneous, and there were significant differences in how the effects were measured. They concluded that the impact of manual therapy on the autonomic nervous system remains unclear and offered their guidance for future studies.…”
Section: Resultsmentioning
confidence: 99%
“…In systematic review studies Roura et al ( 31 ) found that manual therapy may affect both the sympathetic and parasympathetic systems, but the results were inconsistent, the methodology was heterogeneous, and there were significant differences in how the effects were measured. They concluded that the impact of manual therapy on the autonomic nervous system remains unclear and offered their guidance for future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Four reviews searched for changes in biochemical markers or for influence on the autonomic ner- [76] To assess effects of cervical manipulation compared with no treatment, placebo or conventional therapies on pain measurement in patients with degenerative cervical radiculopathy VAS, syndromes in TCM N = 3 trials (502 participants) Each systematic review included a variety of conservative interventions or complex interventions Above all, cervical SM showed significant immediate effects in improving pain scores compared with cervical computer traction. Long-term effects of cervical rotational manipulation were not observed CGHA cervicogenic headache, CROM cervical range of motion, DHI dizziness handicap inventory, HIT-6 Headache Impact Test, HVLA high-velocity lowamplitude thrust, MT manual therapy, MR myofascial release, SM spinal manipulation, NDI neck disability index, NP neck pain, NPQ Northwick Park Neck Pain Questionnaire; NPRS numeric pain rating scale, RCT randomized controlled trial, ROM range of motion, SMT spinal manipulative therapy, TMC traditional Chinese medicine, TTH tension-type headache, VAS visual analogue scale vous system (ANS) after mobilization or MT [35,49,57,58]. Outcome was measured with biochemical markers (neuropeptides, inflammatory and endocrine biomarkers from blood, urine or saliva) or via cardiovascular parameters, skin conductance or skin temperature.…”
Section: Additional Effects Of Manual Medicine Treatmentmentioning
confidence: 99%
“…In other words, changes in ANS balance following treatment precedes changes in pain perception. However, the proposed mechanism of SMT as having an acute positive effect on the ANS balance is questionable [ 17 ], and was challenged in two recent systematic reviews, which concluded that the evidence in favour of such a link was of low or very low quality [ 24 , 25 ]. Also, a recently published randomized trial investigating acute effects of SMT on HRV using a successful sham treatment found no evidence of such an effect over placebo [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different mechanisms have been suggested [14,15], and it has been hypothesized that part of the pain-reducing effects is due to how the treatment influences the ANS balance [14][15][16]. A recent overview of systematic reviews have suggested that acute, short-term sympathetic upregulation can be observed with SMT [17] which has also been suggested with stretching exercises [18][19][20][21][22]. Further, a pain-reducing effect has been observed in a study of patients with persistent or recurrent NP treated with breathing exercises intended to normalize HRV.…”
Section: Introductionmentioning
confidence: 99%